Analisis Profitabilitas Dari Pembiayaan Mudharabah, Musyarakah, Dan Murabahah Pada Bank Umum Syariah Di Indonesia Periode 2005-2010 - Aditya Satriawan; Zainul Arifin (Media Riset Akuntansi, Auditing & Informasi, 2012)
Bank is a business entity that collects funds from the public in the form of savings and channel them to the public in the form of loans or other forms in order to improve the living standards of people. Islamic banking services related to financial services offered by Islamic banks in the packed products that exist in the Islamic bank, one that characterizes the Islamic bank is based financing for the results of mudaraba and musharaka there is also financing by way of sale and purchase or called murabaha. This study aims to determine the effect mudharabah, musyaraka and murabahah to the profitability of Islamic banks in Indonesia as well as which of the three financing is a significant influence on the profitability of Islamic banks in Indonesia. This research uses the object of Islamic banks namely Bank Syariah Mandiri, Bank Mega Syariah, BankMuamalat Indonesia and in the period 2005-2010 the realization of financing (murabahah, musyarakah and mudarabah) using a quantitative method with simple regression analysis that will get the parameters of the effect of changing a variable against other variables, which will then get a conclusion. The study reveals that Return on Equity (ROE), Operating Profit Margin (OPM), and Net Profit Margin (NPM) are significantly affected by mudharabah; and Gross Profit Margin (GPM) is significantly affected by the Musharaka.Keywords: Mudharabah, Musyarakah, Murabahah, ROE, OPM, NPM, GPM